Une lecture grammaticale de séquences choisies dans les échanges philosophiques - Mylène Blasco (Nantes Université, 2016)
This paper proposes an analysis of continuous texts based on a specific corpus made of philosophical discussions. The aim of this syntactic study is to show the inner organization of textual extracts, from their regularities to their variations. After having explained our methodology of analysis of the grammar interactions and of textual visualization - through grid-mapping- our aim is to show, through specifics sequences, how to understand the process of composition. We then give some syntactic hints about the structures framing this work of construction of the text. Our syntactic description on relatively long passages enables us to see more than a simple oral organizational principle; it highlights the outstanding properties of regularity and symmetry the speakers seem to follow in these types of production.